An Examination of the Perceived Importance and Skills Related to Policies and Policy Making Among State Public Health Injury Prevention Staff. Issue 1 (January 2018) - Liller, Karen D.; Chapple-McGruder, Theresa; Castrucci, Brian; Wingate, Martha Slay; Hilson, Renata; Mendez, Dara; Cilenti, Dorothy; Raskind, Ilana
Abstract : Objective: The purpose of this research is to use the Public Health Workforce Interests and Needs Survey to assess in greater detail state injury prevention staff perceptions of policy development and related skills and their awareness and perception of "Health in All Policies" (HiAP). Design: The Public Health Workforce Interests and Needs Survey gauged public health practitioners' perspectives on workplace environment, job satisfaction, national trends, and training needs, and gathered demographics on the workforce. This study utilizes data from the state health agency frame only, focusing solely on those permanently employed, central office staff in injury prevention. Respondents were sampled from 5 paired Health and Human Services regions. Setting/Participants: Approximately 25 000 invitations were sent to central office employees. The response rate was 46% (n = 10 246). The analysis in this article includes only injury prevention employees with programmatic roles, excluding clerical and custodial staff, providing us with a total of 97 respondents. When weighted, this resulted in a weighted population size of 365 injury prevention workers. Main Outcome Measures: The main outcome measures include demographics, responses to understanding of and skill levels related to policy development, and perceptions of HiAP public health trend. Results: State injury prevention workers reported lower policy-making skill but had an overall appreciation of the importance of policies. In general, state injury prevention workers heard of HiAP, thought there should be more emphasis on it, but did not think that HiAP would have an impact on their day-to-day work. Conclusions/Implications for Policy and Practice: Efforts are needed for all state injury prevention workers to become better skilled in policy development, implementation, and evaluation in order to become stronger injury prevention advocates and role models.